(untitled) (American Journal of Islam and Society, 2015)
With the introduction of new educational systems in the Muslim world during the late-eighteenth through the early-twentieth century, many Muslims and non-Muslims became critical of traditional pedagogical methods. In particular, the image of Qur’an schools in West Africa are often criticized for their “backward” forms of education and commonly perceived as places where children simply parrot Qur’anic verses without much understanding. These institutions have largely been abandoned and replaced by modern and secular schooling systems. In his The Walking Qur’an, Rudolph Ware argues that Qur’an schools have survived in places like West Africa. By studying them, he seeks to historicize this once-paradigmatic approach to knowledge. Along with shedding light on Islamic knowledge, Ware attempts to move beyond race by placing Africans at the center of Islamic studies. Such an attempt is welcome, given the rarity of in-depth studies on Islamic history in West Africa. In so doing he makes a welcome contribution to both Islamic and African studies, while simultaneously examining the boundaries between the two ...